Revisiting the Electrochemical Lithiation Mechanism of Aluminum and the Role of Li‐rich Phases (Li1+xAl) on Capacity Fading. Issue 12 (24th June 2019) - Qin, Bingsheng; Diemant, Thomas; Zhang, Huang; Hoefling, Alexander; Behm, R. Jürgen; Tübke, Jens; Varzi, Alberto; Passerini, Stefano
Abstract: Invited for this month′s cover is the group of Stefano Passerini at Helmholtz Institute Ulm. Homepage: http://www.hiu‐batteries.de/battery‐research‐center‐in‐germany/research/electrochemistry/electrochemistry‐for‐batteries/ . The image shows the puzzling electrochemical (de‐)lithiation process of aluminum anode and complex states of aluminum related phase in this course. The Full Paper itself is available at 10.1002/cssc.201900597 . Abstract : " Li‐rich alloys (Li1+ x Al) are not only formed upon deep lithiation but are also always present on the electrode surface…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201900597 . View the Front Cover here: 10.1002/cssc.201901506 .